SISTEM INFORMASI GEOGRAFIS KEBENCANAAN DI KOTA PALU - Ghefra Rizkan Gaffara; Prama Ardha Aryaguna (Jurnal Ilmiah Sistem Informasi, 2021)
Hazard is one of the threats caused by geological factors. Some of geological disasters that occurred in Indonesia are Earthquakes and Tsunamis. This is because Indonesia is geographically located at the confluence of the Asian-Australian plate which has dynamic conditions. So, there is a history of earthquakes and tsunamis in several areas. Palu City is one of the cities that is geographically located on the dynamic plate path. In 2018 there was an Earthquake and Tsunami disaster in Palu City which claimed many lives and materials. It is necessary to have an information system that is spatial in nature to provide information on disaster forecasts (Early Warning System) and also information about the affected areas and estimated losses. By using a Geographic Information System (GIS) areas that have risks can be mapped informatively regarding threats, area coverage and risks to the disaster. This study aims to provide information on the risk of earthquake and tsunami disaster in Palu City and efforts in disaster management in the area